A survey study of physical activity participation in different organisational forms among groups of immigrants and descendants in Denmark - Eva Berthelsen Schmidt; Karsten Elmose-Østerlund; Bjarne Ibsen (BMC Public Health)
Abstract Background Several studies have found that immigrants and descendants are less physically active than the majority population, particularly within sports clubs. However, most studies do not provide breakdowns by specific ethnic groups or organisational forms. Therefore, our paper analyses the influence of ethnicity, immigrant status, and sociodemographic and -economic characteristics on the physical activity participation of immigrants and descendants in sports clubs, commercial centres and self-organised activities in Denmark. Methods Data were collected through a survey study conducted in 2020, with responses from approximately 163,000 adults, of whom eight percent had an immigrant or descendant background. We conducted both a descriptive analysis of the dependent and independent variables and multiple logistic regression analyses, one including the entire sample (including citizens of Danish origin) and one including only citizens with an immigrant or descendant background. Results Our analysis revealed that immigrants and descendants, particularly those of non-Western origin, were significantly less likely than ethnic Danes to be active within the three organisational forms, with the smallest differences observed regarding participation in commercial centres. The analysis also revealed that besides ethnicity, immigrant status and sociodemographic and -economic characteristics were relevant in explaining differences in physical activity participation. Conclusion Our study makes a significant contribution to the literature on physical activity participation among immigrants and descendants from various backgrounds. By utilising a robust sample size and employing statistical analysis, we offer novel insights into participation patterns that have traditionally been explored more qualitatively. Besides the need to study physical activity participation in different organisational forms among different ethnic backgrounds, we also highlight the importance of considering immigrant status and sociodemographic and -economic characteristics in understanding participation behaviours. These findings imply the importance of adopting a holistic and nuanced approach to promoting physical activity participation among immigrant and descendant populations, considering the multifaceted nature of the barriers and facilitators influencing engagement within different organisational settings.